Sistem Penghitung Skor Otomatis Pada Olahraga Menembak Menggunakan Metode Analisis Blob Berbasis Matlab - Hazel Rasendriya Dharma (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2021)
Abstract - Shooting is a sport of agility because this sport requires a high level of focus and accuracy. Currently, the calculation of scores in shooting sports is still using the manual method so that it requires officers and takes longer to calculate scores. The Automatic Scoring System (ASS) in shooting sports aims to classify shooting target images and bullet trail images to calculate the number of scores obtained. The image processing system itself uses the Matlab programming language to detect images on shooting targets. The main principle of the blob analysis method is to detect a collection of pixels with the same color compared to the background in order to detect low-levels in a two-dimensional object. From the testing stage, the percentage of the success of the system in calculating the score is 92%. Compared to the manual/visual calculation method that is still carried out by officers, the ASS System is more effective in calculating scores in shooting sports.